2016
DOI: 10.18632/oncotarget.12326
|View full text |Cite
|
Sign up to set email alerts
|

MDM4rs4245739 A > C polymorphism correlates with reduced overall cancer risk in a meta-analysis of 69477 subjects

Abstract: Mouse double minute 4 (MDM4) is a p53-interacting oncoprotein that plays an important role in the p53 tumor suppressor pathway. The common rs4245739 A > C polymorphism creates a miR-191 binding site in the MDM4 gene transcript. Numerous studies have investigated the association between this MDM4 polymorphism and cancer risk, but have failed to reach a definitive conclusion. To address this issue, we conducted a meta-analysis by selecting eligible studies from MEDLINE, EMBASE, and Chinese Biomedical databases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…MDM4 rs4245739 was intensively studied in different types of cancer [ 18 , 22 , 35 , 36 , 43 , 44 , 45 ]. Part of them [ 35 , 36 ] found no association of this variant with cancer susceptibility, while others [ 22 , 43 , 44 , 45 ] found an association with reduced risk of cancer, mainly of breast cancer but not only. The published results are contradictory, depending on the cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…MDM4 rs4245739 was intensively studied in different types of cancer [ 18 , 22 , 35 , 36 , 43 , 44 , 45 ]. Part of them [ 35 , 36 ] found no association of this variant with cancer susceptibility, while others [ 22 , 43 , 44 , 45 ] found an association with reduced risk of cancer, mainly of breast cancer but not only. The published results are contradictory, depending on the cancer type.…”
Section: Discussionmentioning
confidence: 99%
“… 1 According to molecular epidemiological researches, genetic polymorphisms have been implicated in diverse carcinogenesis mechanisms. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…rs4245739 polymorphism is located in the 3′ untranslated region (UTR) of the MDM4 gene, affects mRNA stability and proteins level [ 31 ]. In this study, we confirmed the impact of MDM4 rs4245739 on ER status, and we consider that AA genotype could indicate better breast cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies observed the associations between single nucleotide polymorphisms (SNPs) in MDM2 and MDM4 genes and various cancers [ 9 , 16 , 23 , 24 , 31 , 32 , 33 , 34 , 35 , 36 ]. In spite of this, the influence on breast cancer has not been sufficiently investigated yet.…”
Section: Introductionmentioning
confidence: 99%